2008
DOI: 10.1038/sj.icb.7100163
|View full text |Cite
|
Sign up to set email alerts
|

‘Iron‐saturated’ lactoferrin is a potent natural adjuvant for augmenting cancer chemotherapy

Abstract: Bovine lactoferrin (bLf), an iron-containing natural defence protein found in bodily secretions, has been reported to inhibit carcinogenesis and the growth of tumours. Here, we investigated whether natural bLf and iron-saturated forms of bLf differ in their ability to augment cancer chemotherapy. bLf was supplemented into the diet of C57BL/6 mice that were subsequently challenged subcutaneously with tumour cells, and treated by chemotherapy. Chemotherapy eradicated large (0.6 cm diameter) EL-4 lymphomas in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(147 citation statements)
references
References 58 publications
8
136
1
2
Order By: Relevance
“…22 Thus far, however, the standard treatment for GBM has been radiotherapy associated with temozolomide (TMZ) chemotherapy. To discover new substances that can improve the standard GBM treatment, we have focused our attention on human lactoferrin (HLF), a natural agent with no toxicity 16 that has been shown to inhibit both the development of experimental metastases 4 in mice and the growth of intestinal, head, and neck cancer in an in vitro human cancer cell model. 8,30 This negative effect of HLF on cell proliferation may be ascribed to the altered expression or activity of regulatory proteins.…”
mentioning
confidence: 99%
“…22 Thus far, however, the standard treatment for GBM has been radiotherapy associated with temozolomide (TMZ) chemotherapy. To discover new substances that can improve the standard GBM treatment, we have focused our attention on human lactoferrin (HLF), a natural agent with no toxicity 16 that has been shown to inhibit both the development of experimental metastases 4 in mice and the growth of intestinal, head, and neck cancer in an in vitro human cancer cell model. 8,30 This negative effect of HLF on cell proliferation may be ascribed to the altered expression or activity of regulatory proteins.…”
mentioning
confidence: 99%
“…The bLf dose for oral therapy was standardized in earlier studies, 15 where we found that 1.2% (w/w) or 12 g Fe-bLf/kg of diet showed no side effects and helped in clearing various tumors. The same dose was then used in our recently published study with a nanoformulated Fe-bLf diet 13 with similar findings.…”
Section: In Vivo Studymentioning
confidence: 99%
“…Therefore, bioavailability of Lf protein at the site of infection does not alter and has shown maximum efficacy. [13][14][15] Earlier successful studies have shown efficacy of these NCs against various tumors 16 and osteoarthritis, 17 and have shown promising results against diseased mice models. Not only Lf protein has been incorporated in these NCs, but also herbal products have been tried against arthritis like diseases, 18 which has divulged multiple availability of these NCs for any drug/molecule/peptide to be loaded.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on bLf, a natural milk protein, have proved its anti-cancer effects and lack of toxicity to normal cells. 15,30,37 In addition to its natural immune-modulation capacity, 17,40 bLf has also been shown to have immune-enhancing and anti-carcinogenic properties, because it can reduce chemically induced tumors in rats and humans. 17,37,[41][42] The key findings of the current investigation suggest the efficient role of Eri silk NPs in carrying anti-cancer bLf proteins and inducing apoptosis using mitochondrial/intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…By supplementing natural bLf (15% iron saturated), Apo-bLf (4% iron saturated), and 50% Fe-bLf into the diet of C57BL/6 mice that were subsequently challenged subcutaneously with tumor cells and were treated by chemotherapy, we found that Fe-bLf was a more potent natural adjuvant for augmenting cancer chemotherapy. 17 A previous study from our laboratory 18 has already established the anti-cancer activities of both Apo-bLf and Fe-bLf in MDA-MB-231 and MCF-7 cells. The results confirmed that the non-nanoformulated form of Apo-bLf induced significantly greater cytotoxicity and reduction in cell proliferation in both types of cancer cells.…”
Section: Introductionmentioning
confidence: 99%